Agronomic sustainability of different farming systems on Alfisols in Southwestern Nigeria - Lal, R. (Informa UK Limited, 1994)
A longterm experiment was conducted on Alfisols at Ibadan, Nigeria, to assess agricultural productivity and sustainability of different farming systems. The experiment, conducted for a 10 year period from 1979 to 1988, was implemented in two phases. The effects of methods of land clearing on crop growth-yield were evaluated during Phase I from 1979 to 1982. Effects of different farming systems on agronomic productivity were evaluated in Phase II from 1983 to 1988. Six land clearing-cum-tillage treatments evaluated in Phase I were: (i) manual clearing with no-till, (ii) manual clearing with plow-till, (iii) shearblade clearing with no-till, (iv) treepusher/rootrake clearing with no-till, (v) treepusher/rootrake clearing with plow-till, and (vi) traditional farming. Similarly, six farming systems evaluated in Phase II were: (i) alley cropping with Leucaena leucocephala, (ii) Mucuna fallowing on severely degraded soils (iii) Mucuna fallowing on moderately degraded soil, (iv) ley farming on severely degraded soil, (v) ley farming on moderately degraded soil, and (vi) natural fallow control. In Phase I, yields of maize (Zea mays), cowpea (Vigna unguiculata) and cassava (Manihoc esculenta) were higher on manually cleared with no-till and shearblade cleared with no-till treatments than on other treatments. In Phase II, maize growth was higher on plots with Mucuna fallowing than in alley cropping or ley farming treatments. In contrast, cowpea growth was higher on alley cropped plots. Regardless of the farming system, maize grain yield declined with the cultivation duration. The relative decline in cowpea grain yield with cultivation duration was less than that of maize.